2014
DOI: 10.1111/cei.12220
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of argatroban and C5a receptor antagonist (PMX53) following intracerebral haemorrhage

Abstract: SummaryIntracerebral haemorrhage (ICH) is a subtype of stroke that associated with neurological dysfunction and inflammation, which may be ameliorated by a neuroprotective strategy targeting the complement cascade. The protective effect of C5a-receptor antagonist (PMX53) solely and in combination with thrombin antagonist (argatroban) was investigated in the ICH mouse model, respectively. Adult male C57BL/6J wild-type (WT) mice and C3 -/-mice were randomized to receive PMX53/argatroban 1, 3 and 5 days after ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…(15, 16) However, whether PHE is an independent predictor of neurologic outcome in human ICH remains controversial, since studies have produced contradictory results. (7, 8, 17) Here we have shown that the rate of PHE expansion predicts outcome after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…(15, 16) However, whether PHE is an independent predictor of neurologic outcome in human ICH remains controversial, since studies have produced contradictory results. (7, 8, 17) Here we have shown that the rate of PHE expansion predicts outcome after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been tested in mouse models for the treatment efficacy of periodontitis, sepsis, intracerebral hemorrhage, and other disorders 33, 34 . PMX53 could significantly reduce C5a-mediated inflammation in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In C5a receptor knockout mice, proinflammatory cytokine levels were decreased in the acute phase after ICH 75 . Moreover, treatment with the C5a receptor antagonist PMX53 in combination with the thrombin antagonist argatroban resulted in decreased mRNA expression of the M1 markers TNF, IL-6 and iNOS in the mouse ICH brain 76 . These data indicate a prominent role for activation of complement C3a and C5a receptors in the proinflammatory response to ICH.…”
Section: Microgliamentioning
confidence: 96%